Multi-component force measurement using embedded fiber Bragg grating - Bhalla, S. (2009)
The development of new fiber Bragg grating (FBG)-based multi-component force sensors is described. A two-component and a three-component force sensor have been fabricated and tested. The two-component force sensor measures the normal and the longitudinal shear component of the force. The three-component force sensor measures the normal, the longitudinal shear and the transverse shear component, and thus provides the magnitude as well as the direction of the force in the three-dimensional space. In the two-component sensor, one FBG is embedded rectilinearly and another non-rectilinearly within carbon composite layer. In the three-component force sensor, one FBG is embedded rectilinearly and two mutually perpendicular FBGs non-rectilinearly within the carbon composite layer. This paper presents the basic sensor structure and the proof-of-concept experimental demonstration of the two sensors. Force measurement within the range 0–15 N has been successfully conducted within 10% deviation.